2013
DOI: 10.1155/2013/832521
|View full text |Cite
|
Sign up to set email alerts
|

Functions, Cooperation, and Interplays of the Vegetative Growth Signaling Pathway in theAspergilli

Abstract: Knowledge on the functions, cooperation, and interplays of the signaling and regulatory pathways of filamentous fungi is crucial when their industrial performance is improved or when new-type antifungals are developed. Many research groups aim at a deeper understanding of vegetative growth signaling because this cascade also influences other important physiological processes including asexual and sexual developments, autolysis and apoptotic cell death as well as the production of a wide array of important seco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 127 publications
(214 reference statements)
0
6
0
Order By: Relevance
“…Fungi seem to choose one of two options, evolving a set of ‘unique’ stress responses or, instead, a ‘general’ stress response. A set of stress-specific “unique” stress responses can provide the fungus with an appropriate adaptation to a wide array of stress but need numerous genes and a complex and robust signaling network to regulate them like that described in the a Aspergilli [ 9 , 48 , 79 , 80 ]. On the other hand, a general stress response can be operated well even with less genes and with a less complex signaling network and can provide the fungi like saccharomycetous yeasts with a perhaps less sophisticated but instantaneous stress response even to cope with impending stress [ 12 , 13 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Fungi seem to choose one of two options, evolving a set of ‘unique’ stress responses or, instead, a ‘general’ stress response. A set of stress-specific “unique” stress responses can provide the fungus with an appropriate adaptation to a wide array of stress but need numerous genes and a complex and robust signaling network to regulate them like that described in the a Aspergilli [ 9 , 48 , 79 , 80 ]. On the other hand, a general stress response can be operated well even with less genes and with a less complex signaling network and can provide the fungi like saccharomycetous yeasts with a perhaps less sophisticated but instantaneous stress response even to cope with impending stress [ 12 , 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…They also demonstrated that stress pre-treatments caused a faster response in gene expression during subsequent high-dose stress treatments, which required the nuclear pore component protein Nup42 [ 83 ]. Furthermore, several studies have demonstrated the overlapping nature of stress signaling pathways with numerous interplays, co-operations and even cross-talks between them [ 8 , 79 , 80 ]. The regulation of this complex and robust network is based on protein-protein interactions and/or modifications rather than on transcriptional changes alone.…”
Section: Discussionmentioning
confidence: 99%
“…4 ; Table 3 ). Further basic questions can include the elucidation of how the various upstream and downstream regulatory elements controlling development, stress, and metabolism in A. nidulans , such as ‘velvet’ proteins 44 45 , SskA and SrrA response regulators 32 33 , SakA mitogen-activated protein kinase 46 and AtfA transcription factor 47 48 contribute to the quality control of mitochondria 4 7 , and understanding how changes in the quality of mitochondrial functions will be sensed and how these signals are channeled towards regulatory elements by specific signaling pathways 49 50 .…”
Section: Discussionmentioning
confidence: 99%
“…Our data in good accordance with these observations in yeast and also support the most recent findings of Emri et al , who challenged the existence of a yeast‐type general stress response in A. nidulans and put emphasis on specific stress responses instead. The filamentous fungus A. nidulans possesses a robust and complex stress response network with functional overlaps as well as with interplays and cross‐talks between the stress signaling and stress response pathways . In a high‐complexity system like this, stress sensitivity phenotypes are often masked by various compensatory mechanisms .…”
Section: Resultsmentioning
confidence: 99%
“…robust and complex stress response network with functional overlaps as well as with interplays and cross-talks between the stress signaling and stress response pathways [19,31]. In a high-complexity system like this, stress sensitivity phenotypes are often masked by various compensatory mechanisms [19].…”
Section: Namementioning
confidence: 99%